A study on the effectiveness of introducing a model of the system for the development of communicative culture of future preschool education teachers under the conditions of master’s degree programs - Kharkivskа A. (Problems of Engineer-Pedagogical Education, 2020)
The article substantiates the stages of the study on the development of communicative culture of future preschool education teachers under the conditions of master’s degree programs, namely: the first stage (2017) dealing with the analysis of scientific, pedagogical, methodological and specialized literature sources to determine the problem as well as the conceptual and terminological apparatus of the study; the second stage (2017–2018) dedicated to defining criteria, indicators, levels of the development of communicative culture of future teachers of preschool education under the conditions of master’s degree programs as well as to conducting the ascertaining stage of the pedagogical experiment and substantiating the structuralfunctional model of the system for the development of communicative culture of future preschool education teachers under the conditions of master’s degree programs; the third stage (2018–2020) dealing with the formative stage of the pedagogical experiment; the fourth stage (2020) dedicated to the control phase of the pedagogical experiment, clarifying practical findings, implementing the literary design of the thesis. The author presents the results of a pilot test on the effectiveness of the model of the system for the development of future preschool education teachers’ communicative culture under the conditions of master’s degree programs. It is substantiated that the introduction of a model of the system for enhancing communicative culture provides positive dynamics in the development of all its components such as communicativereflective orientation, communication literacy, communication ethics, cross-cultural interaction, communicative and organizational readiness. The methodology for calculating the results of the data is presented. Based on generalization of the results of the study, it was found that in the experimental group the percentage of undergraduates with a high level of communicative culture had significantly increased while the percentage of those with a satisfactory level had significantly decreased. This indicates the effectiveness of the developed structural-functional model of the system for the development of communicative culture of preschool education future teachers under the conditions of master’s degree programs. The author comes to the conclusion that the study does not exhaust the whole variety of issues related to the development of the communicative culture of future preschool education teachers. Among the promising areas of further development, the author defines the following: organization of effective management of the development of future preschool education teachers’ communicative culture, continuing training of educators taking into account changes in the regulatory framework and the latest information and communication technology.